Social Spider Optimization On Pid Controller - Yaacob, Noor Diyana (Universiti Sains Malaysia, 2017)
PID controllers are the most widely-used type of controller for industrial applications. They are structurally simple and exhibit robust performance over a wide range of operating conditions. PID is a control loop feedback mechanism systems which is commonly used in industrial control systems. However, finding optimal PID controller parameters is a complicated task. Thus, in order to solve high-dimensional function optimization problem, many swarm intelligence algorithms have been proposed. Among them, Social Spider Optimization (SSO) was chosen for this research. The perfect combination of control parameters proposed may lead to reducing the problems encountered by the industrial plants. The response of the controller can be described in terms of the degree to which the system peak overshoot, Mp, steady-state error, ess, rise time, Tr and settling time, Ts. In addition, appropriate procedures have been established to analyze the quality of Social Spider Optimization (SSO) performance that has been implemented widely in the real world problems. This algorithm is successfully applied in parameters searching for PID controller that shows the accuracy and efficiency to solve such complicated computations.